Penegakan Hukum Lingkungan Sebagai Upaya Membangun Lingkungan Yang Bersih Dan Sehat - Komang Ayu Suseni (Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, 2021)
We can see that the enforcement of environmental laws in Indonesia has not gone as expected. This is made clear by the increasing number and increasing cases of pollution to the environment. The essence of law enforcement actually lies in the factors that might influence it. These factors have a neutral meaning, so that the positive or negative impact lies in the content of these factors. These factors are, as follows: First, the legal factors themselves, in this case are limited to laws only; Second, law enforcement factors, namely the parties who form or implement the law; Third, the factor of means or facilities that support law enforcement; Fourth, community factors, namely the environment in which the law applies or is applied; and Fifth, cultural factors, namely as a result of work, creativity, and human taste. If all these factors work well, the environment will truly provide welfare for the Indonesian people. Kesejahtraan is the creation of a clean and healthy environment.